Dinamika Hubungan Sipil-Militer di Zimbabwe: Dari Pra-Merdeka Hingga Lengsernya Robert Mugabe - Najamuddin Khairur Rijal; Siti Malikatul Mushowwiroh (Department of International Relations, Universitas Andalas, 2018)
This paper study about the dynamics of the civil-military relations in Zimbabwe’s politics. That civil-military relations dynamics tracked since the pre-independence until 2017 at the impeachment of 37 years Robert Mugabe’s power. Two models of civil-military relations according to Huntington, i.e., the subjective and objective civil-military relations is used to analyze the pattern of relationships that formed during the reign of Mugabe. This paper is a descriptive study with data collection through the study documentation. The results indicate that civil-military relations in Zimbabwe takes place dynamically. The early reign of Mugabe puts military on their professionalism. However, in the next, the military used as a political tool to retain power making the pattern of civil-military relations become subjective control. Next, through a constitutional amendment sought to encourage the military to apolitical even though in the end back into the subjective control before finally shedding its support on Mugabe to keep their interests.